REVITALIZATION OF JAVANESE IN SCHOOL ENVIRONMENT IN ERA 4.0: LINGUISTICS LANDSCAPE PERSPECTIVE - Riani - Riani; Tarti Khusnul Khotimah; Nanik Sumarsih (Universitas Negeri Makassar, 2022)
The research discusses the revitalization of Javanese in a school environment from a landscape linguistic perspective. This research is conducted based on the phenomenon that in the era of 4.0 Javanese mastery of the younger generation is inadequate. The data of this research are Javanese texts on public space media placed in the Special Region of Yogyakarta school environment. The research method is carried out by observing, photographing data, classifying data, and analyzing data. The research aims to describe the revitalization of the Javanese in public space media in the school environment from the aspects of language situations, language codes, Javanese writing order, written form, form, function, and local wisdom values. The results show that the revitalization of the Javanese language based on situation aspects and language codes are divided into three types, namely monolingual (Javanese), bilingual (Javanese and Indonesian), and multilingual (Javanese, Indonesian, English, and Arabic). Based on the order of writing, Javanese is placed in the order of first, second, third, fourth, and only Javanese. Based on the form of writing, Javanese is categorized into three types, namely Javanese, Latin character, and a combination of Javanese and Latin. Based on the form realization, Javanese is classified into eight types, namely room names, expressions, phatic expressions, proverbs, philosophies, appeals, prose, and slogans. Based on the function, Javanese is categorized into four types, namely information, advice, appeal, and greeting. Based on the values of local wisdom, Javanese contains teachings about ethics and morals, philosophy of life, religion, preserving the environment, maintaining health, tolerance, work ethic, cooperation, and preserving Javanese script.